1996
DOI: 10.1097/00004728-199601000-00005
|View full text |Cite
|
Sign up to set email alerts
|

Use of Spirometry to Predict Risk of Pneumothorax in CT-Guided Needle Biopsy of the Lung

Abstract: We conclude that decreasing FEV1 is associated with a higher pneumothorax rate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
33
1

Year Published

2000
2000
2014
2014

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(42 citation statements)
references
References 14 publications
8
33
1
Order By: Relevance
“…It is generally accepted that patients with a long-term smoking history and severe chronic obstructive lung disease (COPD) are at greater risk for adverse complications from the procedure. The severity of the underlying lung disease has been reported to be one of the determining risk factors for pneumothorax [3,4,5,6,7]. The trend in percutaneous needle biopsy technique has been to replace FNAB with core-needle biopsy in order to reduce the frequency of nondiagnostic biopsy procedures [11,12,13].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is generally accepted that patients with a long-term smoking history and severe chronic obstructive lung disease (COPD) are at greater risk for adverse complications from the procedure. The severity of the underlying lung disease has been reported to be one of the determining risk factors for pneumothorax [3,4,5,6,7]. The trend in percutaneous needle biopsy technique has been to replace FNAB with core-needle biopsy in order to reduce the frequency of nondiagnostic biopsy procedures [11,12,13].…”
Section: Discussionmentioning
confidence: 99%
“…The reported incidence ranges from 8 to 54%, with 1.6-17% of patients requiring chest tube drainage [1,3]. Chronic obstructive pulmonary disease (COPD) is considered to be one of the primary contributing factors for the development of post-FNAB pneumothorax [3,4,5,6,7].…”
Section: Introductionmentioning
confidence: 99%
“…In COPD, more severe disease with FEV 1 less than 1 L has been reported to be associated with increased risk of developing secondary spontaneous pneumothorax (1,19). The risk of iatrogenic pneumothorax has been associated with the qualitative appearance of emphysema on chest CT scans (20,21). The association of iatrogenic pneumothorax with spirometry values is not clear, as two studies have showed inconsistent results (21,22).…”
mentioning
confidence: 99%
“…The risk of iatrogenic pneumothorax has been associated with the qualitative appearance of emphysema on chest CT scans (20,21). The association of iatrogenic pneumothorax with spirometry values is not clear, as two studies have showed inconsistent results (21,22).…”
mentioning
confidence: 99%
“…The severity of underlying lung disease has been correlated with the rate of pneumothorax during percutaneous needle aspiration [64, 65, 66, 67, 68, 69]. No similar bronchoscopic studies exist.…”
Section: Discussionmentioning
confidence: 99%